The Effect of Shallot Compresses on Decreasing Body Temperature in Children With Fever - Mardhiah (Talenta Publisher, 2022)
One of the non-pharmacological treatment of fever in children is shallot compresses. This study aims to determine the effect of shallot compresses on decreasing body temperature in children with fever. This research used a quasi-experimental one group pre-posttest design and used simple random sampling as the sampling technique. A digital thermometer and observation sheet were used as the research instruments. The research took the data of children's temperature 2 times (pretest, posttest 15 minutes). The sample of this study was 20 children aged 3-6 years old. This study uses the normality test with Shapiro-Wilk and parametric statistical analysis of the Paired Test. The results showed that most child's temperature before being treated with shallot compress was 37.8ÂºC (25%) and most of the child's temperature after being treated with shallot compress was 37.0ÂºC (30%). A significant value of 0.000 (Ë‚0.05) means that there is a difference in body temperature before and after the shallot compress. Based on the results, shallot compresses can reduce children's body temperature when they have a fever. It can be used as early treatment for children with fever.